Femtosecond Laser Ablation of Polymer Thin Films for Nanometer Precision Surface Patterning - 전인동; 이지욱; 옥명렬; 김유찬; 전호정 (한국표면공학회, 2016)
Femtosecond laser ablation of ultrathin polymer films on quartz glass using laser pulses of 100 fs and centered at λ=400 nm wavelength has been investigated for nanometer precision thin film patterning. Singleshot ablation craters on films of various thicknesses have been examined by atomic force microscopy, and beam spot diameters and ablation threshold fluences have been determined by square diameter-regression technique. The ablation thresholds of polymer film are about 1.5 times smaller than that of quartz substrate, which results in patterning crater arrays without damaging the substrate. In particular, at a 1/e2 laser spot diameter of 0.86 μm, the smallest craters of 150-nm diameter are fabricated on 15-nm thick film. The ablation thresholds are not influenced by the film thickness, but diameters of the ablated crater are bigger on thicker films than on thinner films. The ablation efficiency is also influenced by the laser beam spot size, following a w0q -0.45 dependence.